1992
DOI: 10.1007/bf00444361
|View full text |Cite
|
Sign up to set email alerts
|

The AXB and BXA set of recombinant inbred mouse strains

Abstract: The recombinant inbred (RI) set of strains, AXB and BXA, derived from C57BL/6J and A/J, originally constructed and maintained at the University of California/San Diego, have been imported into The Jackson Laboratory and are now in the 29th to 59th generation of brother-sister matings. Genetic quality control testing with 45 proviral and 11 biochemical markers previously typed in this RI set indicated that five strains had been genetically contaminated sometime in the past, so these strains have been discarded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…BXD strains are inbred lines derived from brother-sister matings starting from an F 2 cross (12,13). AXB͞BXA are based on reciprocal intercrosses between C57BL͞6J and A͞J (14). Animals were kept in conventional laboratory cages with standard food and access to food and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BXD strains are inbred lines derived from brother-sister matings starting from an F 2 cross (12,13). AXB͞BXA are based on reciprocal intercrosses between C57BL͞6J and A͞J (14). Animals were kept in conventional laboratory cages with standard food and access to food and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Strains DBA͞2J and A͞J show particularly large differences in adult neurogenesis from the canonical mouse strain, C57BL͞6J (1). In this study, we explored natural variation in adult hippocampal neurogenesis in two complementary sets of recombinant inbred (RI) strains of mice (BXD and AXB͞BXD), which represent inbred progeny of F 2 crosses from C57BL͞6J and DBA͞2J (BXD), and C57BL͞6J and A͞J (AXB͞BXA) (12)(13)(14). On average, and in large panels, each RI strain shows an Ϸ50:50 pattern of genome inherited from the parental strains and is homologous at every locus.…”
mentioning
confidence: 99%
“…These advantages include the development of diverse and unique genetic resources, including completion of a detailed map of murine genomic sequence that is freely available through the internet, as well as Ͼ450 inbred strains of mice that have been generated over the past century, with each strain genetically being homogeneous and offering a unique array of phenotypes (8,9). The availability of murine embryonic stem cells has also provided the ability to disrupt the expression and function of specific preselected genes (10 -12).…”
Section: Iabetic Nephropathy (Dn) Is the Major Single Cause Of Esrdmentioning
confidence: 99%
“…This artificial introgression of genetic heterogeneity in inbred mouse populations must not be considered more than an involuntary human error, although with relevant consequences if the resulting abnormal mice are used for research. Several studies have revealed contamination in experimental breeding stocks of mice (West et al, 1985;Marshall et al, 1992;Nandakumar and Holmdahl, 2005;Nitzky et al, 2007), leading to an additional source of allogenicity.…”
Section: Contaminationmentioning
confidence: 99%